Outcomes of Coronectomy and Total Odontectomy of Impacted Mandibular Third Molars - Shehab Ahmed Hamad (Elsevier, 2024)
Objective: The aim of this research was to evaluate the surgical complications and neurosensory deficits after coronectomy and the complete removal of mandibular third molars. Methods: The study sample included patients requiring surgical removal of mandibular third molars. A coronectomy was conducted on 220 teeth showing signs of close proximity to the inferior alveolar canal. A complete extraction was performed on 218 teeth with no risk signs. The patients were evaluated at 1 week and 1, 3, 6, 12, and 24 months after surgery for pain, swelling, neurologic deficit, dry socket, postoperative bleeding, infection, root migration, and eruption. Results: No significant difference was noted in pain and swelling; however, bleeding and dry socket were significantly higher in the odontectomy group (P = .017). The inferior alveolar nerve deficit was higher in the odontectomy group (3.7%) than the coronectomy group (0.5%) (P = .017). The percentage and distance of root migration of coronectomised teeth at 3, 6, and 12 months were 60% (2.37 ± 0.96 mm), 66% (3.35 ± 0.86 mm), and 74% (3.85 ± 0.93 mm), respectively. Conclusions: Coronectomy is a safe procedure and should be performed when the roots are closely associated with the mandibular canal. Although root migration is common, the likelihood of root exposure is low and roots rarely need removal.